2020
DOI: 10.1186/s12884-020-02878-z
|View full text |Cite|
|
Sign up to set email alerts
|

Antenatal cervical length measurement as a predictor of successful vaginal birth

Abstract: Background: Antenatal cervical length measurement has paramount importance in the prediction of labor. It was compared to the Bishop Score and incorporated in the modified Bishop score due to its relevance and convenience. It is a more accurate tool that imposes no harm or distress to the patients. The study aimed to evaluate the role of antenatal cervical length measurement in the prediction of a successful vaginal birth and its relation to the duration of labor. Methods: This was a prospective cohort study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…14 Moreover, CL measurements play a major role in the prediction of labor . 15 Although standard measurements for uterine CL with increasing gestational age are not available yet, several studies have provided reference ranges (measured by TVUS) in large populations of women with singleton pregnancies . 16 An inverse relation between the uterine CL during pregnancy and the frequency of PTD has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…14 Moreover, CL measurements play a major role in the prediction of labor . 15 Although standard measurements for uterine CL with increasing gestational age are not available yet, several studies have provided reference ranges (measured by TVUS) in large populations of women with singleton pregnancies . 16 An inverse relation between the uterine CL during pregnancy and the frequency of PTD has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Prediction models for successful delivery through ultrasound include cervical length, angle of progression (AOP), fetal headperineum distance (HPD), fetal head-symphysis pubis distance (HSD), fetal head position before labor, sono-elastography, and shear wave velocity, which allow the assessment of cervical stiffness in pregnancy [7]. Although studies on cervical length as a predictor of delivery mode have been conducted widely, the results are controversial [8][9][10][11][12]. Sonoelastography has been introduced recently and proven to be useful for predicting the outcome of induced labor; however, this technique it is unsuitable for general use because of expensive equipment and the requirement of high-level skills.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant predictor is parity, whereby our study showed that one previous vaginal delivery will increase the odds of having a successful induction by 2.7 times. This was also an established independent factor from other published studies [12,26,28,29].…”
Section: Discussionmentioning
confidence: 69%